Impregnation of Nanoparticle Scaffolds for Syngas-Fed Solid Oxide Fuel Cell Anodes. (2nd June 2015) - Boldrin, Paul; Ruiz-Trejo, Enrique; Tighe, Christopher; Chang, Kee-Chul; Darr, Jawwad; Brandon, Nigel P.
Abstract : A strategy for fabrication of solid oxide fuel cell anodes with improved porosity and lower sintering temperatures by impregnation of nanoparticle-containing porous scaffolds of ceria-gadolinia (CGO) has been developed. The CGO scaffolds are fabricated using a screen-printed ink containing nanoparticles and commercial particles of CGO and polymeric pore formers. Scanning electron microscopy and in situ ultra-small angle X-ray scattering show that incorporation of nanoparticles increases the porosity by allowing a reduction in sintering temperature. Electrochemical characterisation of symmetrical cells shows that the cells sintered at 1000 °C possess similar electrode polarisation compared to those sintered at 1300 °C. Button cell testing showed that reducing the sintering temperature produced cells which perform better at 700 °C and below in hydrogen, and performed better at all temperatures using syngas. This approach has the potential to allow the use of a wider range of nanomaterials, giving a finer control over microstructure.